The use of infrared thermography to verify corrosion on reinforced concrete posts (Research, Society and Development, 2022)
The infrared thermography can show, in a non-destructive way, pathological manifestations before them becoming visible and more harmful, due to the existence of inconsistencies in the thermal patterns of the elements of the structure that exhibit pathological manifestations. The thermal evaluation with basis on thermography is the perception of the superficial temperature of a body through the heat transfer mechanism), once every body with temperature above absolute zero emits thermal radiation. This study aims to qualitatively analyze the use of digital thermal experiment in order to detect the occurrence of corrosion in posts made of reinforced concrete located on Olinda's beachfront (PE). The experiments were performed on 10 posts between 14 and 15 o'clock, with verification on the front side (with direct activity of salty spray), and on the back side. The equipment used was a thermal camera, FLIR E-60. The surroundings of the experiments have environmental aggressiveness level IV (very intense), with elevated risk of deterioration. In the experiment analysis, it is possible to verify that the corrosion products conduct more heat, presenting a higher temperature than on the concrete, therefore, the search for the occurrence of corrosion is related to the detection of temperatures higher than the ones verified as a tendency in concrete. The experiments showed that an elevated temperature in concrete cracks may be an indication of the occurrence of corrosion on reinforcements, as well as, through the analysis of thermograms were identified indications of corrosion on the analyzed structure.